MEMBANGUN KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG PRODUK SCARLETT WHITENING MELALUI HARGA, CELEBRITY ENDORSER, DAN CITRA MEREK - Annisya Bunga Pertiwi; Mahmud Mahmud (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The purpose of this study is to analyze the effect of price, celebrity endorser, and brand image on purchasing decisions and repurchase intention of Scarlett Whitening Products (Study of Scarlett Whitening Product Users in Central Java Province). The population of this study are consumers of Scarlett Whitening users in Central Java Province. Data were collected by distributing questionnaires to 120 respondents using a purposive sampling method. The analytical method used in this research is multiple linear regression analysis, instrument test, classical assumption test, coefficient of determination, f test, and T test. The results of this study show that price, celebrity endorser, and brand image have a positive and significant effect on purchasing decisions. Price, Celebrity Endorser, Brand Image, and Purchase Decision have a positive and significant effect on repurchase intention.